How Does Artificial Intelligent Impact the Likelihood of Repurchase Intention? - Adrian, Muhammad Arman Revo; Wahab, Muhammad Abdul; Wanda Novita (PT Aksara Indo Rajawali, 2025)
This study explores the impact of AI-driven product recommendations and chatbot quality on consumer repurchase intention on the Shopee platform, with consumer consideration as a mediating factor. Data were collected through a questionnaire distributed on social media, targeting Shopee users who had previously made purchases. A total of 155 respondents were selected via purposive sampling, and the data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) in SmartPLS 3.0. The results show that AI-based product recommendations do not significantly influence consumer consideration or repurchase intention (p = 0.191 and p = 0.974). In contrast, chatbot quality significantly impacts both consumer consideration (p = 0.000) and repurchase intention (p = 0.004). Additionally, consumer consideration mediates the relationship between chatbot quality and repurchase intention (p = 0.000). These findings suggest that while AI product recommendations are ineffective in driving repeat purchases, high-quality chatbots play a crucial role in enhancing consumer engagement and loyalty. The study provides insights into the effectiveness of AI in e-commerce marketing and emphasizes the importance of chatbot quality in fostering consumer satisfaction and repurchase intention.